Pengaruh Kepemimpinan Kepala Desa, Pengetahuan, dan Sosialisasi Pemungutan Pajak Bumi Dan Bangunan Terhadap Penerimaan Pajak Bumi dan Bangunan Pada Tahun 2021 : (Studi Kasus Pada Kecamatan Marga Tiga) - Wayan Septianawati; Eksa Ridwansyah; Lihan Rini Puspo Wijaya (Jurnal Ilmiah ESAI, 2023)
This study aims to determine the effect of Village Head Leadership, Knowledge, and Socialization of Land and Building Tax Collection on Land and Building Tax Revenue in 2021 (Case Study in Marga Tiga District). The data used are primary data carried out by distributing questionnaires. The samples used in this study were 100 respondents who met the sample criteria from the total population of the community who became land and building taxpayers in Marga Tiga District. This study uses multiple linear regression analysis.  The results of this study indicate that (1) the leadership of the village head has no significant effect on land and building tax revenues in 2021 in Marga Tiga District. (2) Knowledge of Land and Building Tax Collection has a significant effect on land and building tax revenues in 2021 in Marga Tiga District. (3) Socialization of Land and Building Tax Collection has a significant effect on land and building tax revenue in 2021 in Marga Tiga District.  (4) Village Head Leadership, Knowledge, and Socialization of land and building tax collection have a significant effect on land and building tax revenue in 2021 in Marga Tiga District.